A STUDY ON EMPLOYEE SATISFACTION OF FRUIT PROCESSING INDUSTRIES IN KRISHNAGIRI DISTRICT - R. SENGODI; MADHESH, Dr. C. (The journal of contemporary issues in business and government, 2021)
The fruit processing industry plays an important role in Krishnagiri district. Krishnagiri district is mostly associated with agriculture and consists mostly of fruit growers. Hence this study emphasizes on evaluating the job satisfaction of the employees who contribute to the progress of the fruit processing Industry. Job satisfaction occurs when an employee has job stability, career development and a comfortable work life balance. It refers to the employee's job satisfaction as the job meets the individual's expectations. This study focuses on the employee satisfaction of fruit processing industry in Krishnagiri district. The sample size consists of a total of 55 employees from 5 companies of Paiyur. Paiyur have highest number of fruit processing companies. Primary information has been collected from the fruit processing industry divisions in Krishnagiri district. Statistical tools used were percentage analysis, Chi-square analysis and ANOVA.